PERAN CITRA TUBUH, FAKTOR SOSIAL EKONOMI, KUALITAS KONSUMSI PANGAN DAN HUBUNGANNYA DENGAN KEJADIAN KEK PADA WANITA USIA SUBUR DI KECAMATAN MENES KABUPATEN PANDEGLANG - Fauziah, Firli Isda; Ashari, Chica Riska (Jurnal Gizi dan Pangan Soedirman, 2024)
Chronic energy deficiency (CED) is a condition resulting from prolonged or chronic lack of food intake, especially energy and protein, and is characterized by Mid-upper Arm Circumference (MUAC) < 23.5 cm. The CED can occur due to low socio-economic status and dissatisfaction with the body, which will affect the lack of variety of food consumed. This research aims to see the relationship between socio-economic status, quality of food consumption and body image on the incidence of CED among women of reproductive age (WRA) in Menes District, Pandeglang Regency. This research is quantitative research with a cross sectional design, and analyzed using the Chi Square test. The sample was determined using purposive sampling and obtained 123 respondents. Data collection was carried out by measuring MUAC, 2x24 hour recall and interviews using socioeconomic status questionnaires, women dietary diversity score (WDDS) and Body Shape Questionnaire (BSQ-16). The results of the study showed that 29.3% of respondents experienced CED, which shows that there is a relationship between recent education (p = 0.036), income (p = 0.009), and body image (p = 0.005) with the incidence of CED among WRA in Menes District, Pandeglang Regency. The research results also show that there is no relationship between nutritional knowledge (p = 0.106), employment (p = 0.364), and quality of food consumption (p = 0.392) with the incidence of CED among WRA in Menes District, Pandeglang Regency. The conclusion of this research is that the incidence of KCED in WRA can be influenced by education, income and body image.